Estado nutricional y presencia de acné en los estudiantes del colegio 27 de febrero periodo 2012 - Iñahuazo Solano, Diana Margarita (2014)
This cross-sectional study, descriptive, dealing with nutritional status and presence of acne on tax college students mixed "February 27" period 2012, whose main objective is to understand the influence of changes in nutritional status in the presence of Acne in eleventh grade students from school Feb. 27. The study sample comprised students of eleventh grade being 212 students, aged 14 to 17 years, with 90 men and 122 women. Participants were measured height and weight thus calculated the Body Mass Index (BMI). Profile and psycho-emotional status was assessed by survey. The presence, extent and location of acne was assessed by history and physical examination. The results indicate that 62.3% of the population has normal weight, but excess weight affects 35.9% of adolescents: 28.8% overweight and 7.1% obese, underweight 1 , 9%. The presence of acne was presented in 73% of adolescents, 40% men and 60% women with increased incidence in overweight women to 68%, with no relation underweight, normal or obese. Teens in which association had been altered by excess nutritional and social condition acne had considerable percentage, with women affected in 45% while men with 38%. Taken together these data indicate significant association of nutritional status in the presence of excess acne especially overweight, needed immediate intervention measures to prevent and treat these serious public health problems. Words key: adolescence, nutritional state, acne.